FIRST RECORD OF OCNERODRILID EARTHWORM FROM SELECTED REGION OF THE GANGETIC PLAIN OF BIHAR, INDIA - ROHIT SRIVASTAVA,; MRIDULA KUMARI,; MANOJ KUMAR,; RAKESH RANJAN,; MANORANJAN PRASAD SINHA, (The Bioscan, 2023)
Owing to nonavailability of any report on earthworms belonging to family Ocnerodrilidae, the present survey was conducted in the Gangetic plain region of Bihar. A single species Ocnerodrilus occidentalis Eisen was recorded during the survey representing the genus Ocnerodrilus Eisen of the family. This species has been reported from different parts of India. The paper deals with details of its diagnosis.